Assay of Efavirenz by Visible Spectrophotometric Methods - Bikshambabu, A.; Ramu, G.; Rambabu, C. (Asian Journal of Chemistry, 2011)
Two simple, rapid and sensitive spectrophotometric methods have been developed to determine the amount of efavirenz in pure form. Method-A is based on the reaction of the drug with 1,2- naphthaquinone-4-sulphonic acid to form N-alkylamono naphthaquinone. In method-B, estimation is based on the reduction of ferric ions to ferrous ions by the drug, which forms green coloured chromogen in the presence of potassium ferricyanide. Beer's law is obeyed in the concentration ranges 2.0-12.0 μg mL-1; 5.0-30.0 μg mL-1, respectively. The molar absorptivity and % RSD are 2.45 × 104; 5.43 × 103 Lt mol-1 cm-1 and 3.29 and 0.78 for methods A and B respectively.